PERAN TOKOH AGAMA ISLAM DI DAERAH MINORITAS MUSLIM SEBAGAI PEMBENTUK SOSIAL KEAGAMAAN: (Studi Kasus Desa Sukajulu, Kecamatan Barusjahe, Kabupaten Karo) - Dira Azzahra Putri; Suheri Harahap; Ahmed Fernanda Desky (CV. Denasya Smart Publisher, 2024)
Minority groups usually have difficulty getting the access they need in their areas. As a Muslim minority community living in a non-Muslim majority environment, they definitely need religious knowledge for their lives as Muslims. And this makes the role of religious figures very important in teaching and providing Islamic religious knowledge. The aim of this research is to identify the role of religious figures in the social development of religion in society, especially in situations where Muslims are a minority. This research uses qualitative methods with a descriptive approach to study the role of religious figures in Sukajulu village. Data collection techniques in this research used observation, interview and documentation techniques. The theory used to analyze this phenomenon is Emile Durkheim's theory of social solidarity. The results of this research show that the role of religious figures in Sukajulu village is still relatively lacking, because there are no religious figures who live in this village. The religious figures who serve here never last long, and this results in frequent changes in religious figures. Sukajulu village is a Muslim minority village which should receive more attention from religious leaders. Even though there is a lack of religious figures in this village, the religious activities of the minority community in Sukajulu village are still ongoing.